Determination of intrafraction prostate motion during external beam radiation therapy with a transperineal 4-dimensional ultrasound real-time tracking system - Sihono, Dwi Seno Kuncoro; Ehmann, Michael; Swietochowski, Sandra von; Grimm, Mario; Boda-Heggemann, Judit; Wenz, Frederik; Wertz, Hansjörg (International journal of radiation oncology, biology, physics, 2018)
Purpose/Objective - To determine intrafraction prostate motion during volumetric modulated arc therapy (VMAT) using transperineal ultrasound (US) real-time tracking. - Methods and Materials - 770 US monitoring sessions in 38 prostate cancer patients' VMAT treatment series were retrospectively evaluated. Intrafraction motion assessment of the prostate was based on continuous position monitoring with a 4-dimensional US system along the 3 directions: left-right (LR), anterior-posterior (AP), and inferior-superior (SI). The overall mean values and standard deviations (SD) along with random and systematic errors were calculated. - Results - The mean duration of each monitoring session was 254 s. The mean (μ), the systematic error (Σ), and the random error (σ) of intrafraction prostate displacement were μ = (0.01, −0.08, 0.15) mm, Σ = (0.30, 0.34, 0.23) mm, and σ = (0.59, 0.73, 0.64) mm in the LR, AP and SI directions, respectively. The percentage of treatments for which prostate displacement was ≤2 mm was 97.01%, 92.24%, and 95.77% in the LR, AP, and SI directions, respectively. At 60 s, a vector length of prostate displacement >2 mm was present in 0.67% of the data. The percentage increased to 2.42%, 6.14%, and 9.35% at 120 s, 180 s, and 240 s, respectively. - Conclusions - The magnitudes of intrafraction prostate motion along the SI and AP directions were comparable. On average, the smallest motion was in the LR direction and the largest in AP direction. Most of the prostate displacements were within a few millimeters. However, with increasing treatment time (eg, during hypofractionation), larger 3-dimensional prostate displacements up to 18.30 mm could be observed. Shortening treatment time can reduce the impact of intrafraction motion and potentially allows smaller safety margins.